7(x-7)+10=4(x-6)

Simple and best practice solution for 7(x-7)+10=4(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-7)+10=4(x-6) equation:


Simplifying
7(x + -7) + 10 = 4(x + -6)

Reorder the terms:
7(-7 + x) + 10 = 4(x + -6)
(-7 * 7 + x * 7) + 10 = 4(x + -6)
(-49 + 7x) + 10 = 4(x + -6)

Reorder the terms:
-49 + 10 + 7x = 4(x + -6)

Combine like terms: -49 + 10 = -39
-39 + 7x = 4(x + -6)

Reorder the terms:
-39 + 7x = 4(-6 + x)
-39 + 7x = (-6 * 4 + x * 4)
-39 + 7x = (-24 + 4x)

Solving
-39 + 7x = -24 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-39 + 7x + -4x = -24 + 4x + -4x

Combine like terms: 7x + -4x = 3x
-39 + 3x = -24 + 4x + -4x

Combine like terms: 4x + -4x = 0
-39 + 3x = -24 + 0
-39 + 3x = -24

Add '39' to each side of the equation.
-39 + 39 + 3x = -24 + 39

Combine like terms: -39 + 39 = 0
0 + 3x = -24 + 39
3x = -24 + 39

Combine like terms: -24 + 39 = 15
3x = 15

Divide each side by '3'.
x = 5

Simplifying
x = 5

See similar equations:

| 5w^2-26w=24 | | 8x^6+999x^3-125=0 | | 14-6(x+1)=12-4(x+3) | | 3t^2-13t=10 | | 11(a-6)=-5-6 | | 3(5x+1)+5(x-2)= | | z^2*z^4= | | -6(-11t-7+9c)= | | -6x-3x=18 | | 0.5(8-x)=8 | | 5x^2+4x+1=0 | | p^3-p^2-4p+4=0 | | x^5-x^3+8x^2+8=0 | | 3x^2=-6x | | -11+3x=40 | | F=2e-8 | | 6r^2+23r*20=0 | | -7x+4(2x-3)=-17 | | s*s=42 | | 4x^2+14x-30=0 | | -2x+2(4x+13)=-10 | | 5x+1=-3x-63 | | 2x^3+10x^2-28x=0 | | 2x+5=x+7 | | y=(x+1)2 | | 77=10x-53 | | 6x+9=8x-13 | | 3(x+3)=2(x+5) | | 7x+5(-4-13)=-169 | | 4x+50=8x-10 | | -9=-4+x/13 | | 83-3x=15x+21 |

Equations solver categories